Manufacturing excellence: the labor process and action logic of Chinese professional basketball players - Sun, Z.; Xiaofei, X. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Since the founding of the Peoples Republic of China, the field of competitive sports has achieved remarkable accomplishments that have garnered worldwide attention. Among the most important participants are professional athletes, who serve as both the "backbone of the nation" when representing the country in competitions and as "ascetics" during the rigorous training outside of competitions. Unlike many other laborers, the subject and object of labor in the process of athletes work are highly unified. Competitive sports entail great uncertainty and intense competition, and athletes often bear the honor of their localities or the nation. Through sports and competitions, they undertake significant social functions and responsibilities. Given the unique nature of the labor and identity of Chinese professional athletes, their work sites, labor processes, and labor orders should be areas of focus for sport sociology. Base on the questionnaire survey and deep interviews*this study claims that*"competition and solidarity," a labor form seemingly filled with internal tension, cleverly and efficiently governs the entire labor process of professional basketball players throughout their sporting careers. Its institutional and cultural logic constitute a complete mechanism for "manufacturing excellence" in Chinese competitive sports. This operational logic presents a scene that appears contradictory yet possesses profound internal coherence: in an industry requiring high-intensity physical labor and complex technical labor, managers meticulously control athletes labor production and reproduction time, activity spaces, and physical management to maximize and maintain their competitive abilities throughout their limited sporting careers. Athletes, in turn, express acceptance and support for this management approach, even willingly engaging in the "rushing game" and "consent" dominion logic closely linked to self, collective, and national honor. Based on this logic, the dominant form of labor control is both institutional and cultural, with a series of emotionally charged stimuli associated with honor and spirit actively engaging athletes. The practice of this operational mechanism depends on the internal labor market of the three-tier training network under Chinas nationwide system, as well as the athletes high degree of national identity and pursuit of honor, materializing it into emotional labor. This process is closely related to the ideological functions and cultural characteristics unique to competitive sports. Through the analysis of the labor field and processes of professional basketball players, this research claims that besides the dimensions of internal labor markets and national institutional constraints, the introduction of sports ideology and culture into the analytical framework can reveal another logic of labor processes where professional basketball players not only "manufacturing consent" but also strive to "manufacturing excellence."